DEMOKRASI KONSTITUSIONAL DALAM PENYELENGGARAAN NEGARA (Studi Analisis Pemikiran KH. Wahab Chasbullah) - Tabrozi, Dhika; B. Syafuri; Faisal Zulfikar; David Nugraha Saputra (Al Qisthas Jurnal Hukum dan Politik, 2023)
Democracy is very fundamental in the administration of the state based on the principles of popular sovereigbty, deliberation and consensus, not on personal, group or class interests. Constitutional democracy is the answer in limiting arbitrary government actions which is a fundamental principle based on Pancasila and the 1945 Constitution as the state constitution. This research uses a qualitative approach (literature review). The result of research on constitutional democracy based on the author’s analysis of Wahab Chasbullah’s thoughts are divided in two principles. First. The implementation of constitutional democracy is based on the principles of Islamic law which consists of asy-syuro, al-‘adalah, al-hurriyah an al-musawa and by maintaining human rights guarantees. Second. The implementation of democracy based on the objectives of Islamic law (maqashid asy-syariah) is the vision of Islamic law towards (hifdz ad-din), (hifdz an-nafs), (hifdz al-‘aql), (hifdz an-nasl), (hifdz mal). By paying attention to the protection of human honor (hifdz al-‘irdh), and the protection of the environment (hifdz al-bi’ah)